TERAPI SEFT (SPIRITUAL EMOTIONAL FREEDOM TECHNIQUE) UNTUK MENGHADAPI KECEMASAN DALAM PERSALINAN - Widiyanti Sarimunadi; Bunga Tiara Carolin; Rosmawaty Lubis (JKM (Jurnal Kebidanan Malahayati), 2021)
ABSTRACT: SEFT THERAPY (SPIRITUAL EMOTIONAL FREEDOM TECHNIQUE) FOR ANXIETY IN DEALING WITH LABORBackground: If the concern and anxiety of pregnant women is not handled seriously, it will have an impact and influence on physical and psychological aspects, both on the mother and the fetus. Pregnant women who experience anxiety in the face of labor are afraid of being operated on, afraid of spending a lot of money, fear of not being able to care for their babies properly, fear of their baby dying, fear of pain during delivery. One of the techniques for dealing with anxiety is SEFT therapy.Objective: to determine the effect of Spiritual Emotional Freedom Technique (SEFT) on anxiety in dealing with labor process.Methodology: this research is a quasi-experimental design with pre and post-test with control group design. The sample in this study was 25 trimester III pregnant women. The sampling technique was using purposive sampling technique. The research instrument used the DASS 42 questionnaire. The results of the data normality test were normally distributed so that the data were analyzed using the paired t-test.Results: The results showed that the average score of maternal anxiety before therapy was 13.48 (moderate) while after therapy was 7.88 (normal). The bivariate test results obtained p value 0,000.Conclusions: Spiritual Emotional Freedom Technique (SEFT) can overcome the anxiety of pregnant women in facing labor.Suggestions: It is hoped that this therapy can be applied in the practice of midwifery to care for pregnant women, especially pregnant women who experience trauma or have anxiety in their pregnancy. Keywords: anxiety, pregnant women, spiritual emotional freedom technique. ABSTRAK Latar Belakang: Kekhawatiran dan kecemasan pada ibu hamil apabila tidak ditangani dengan serius akan membawa dampak dan pengaruh terhadap fisik dan psikis, baik pada ibu maupun janin. Ibu hamil yang mengalami kecemasan dalam menghadapi persalinan disebabkan karena ibu takut dioperasi, takut akan mengeluarkan biaya yang banyak, takut tidak bisa merawat bayinya dengan baik, takut bayinya meninggal, takut kesakitan saat persalinan. Salah satu teknik untuk menghadapi kecemasan adalah denga terapi SEFT.Tujuan: Mengetahui pengaruh Terapi Spiritual Emotional Freedom Technique (SEFT) terhadap kecemasan dalam menghadapi persalinan.Metodologi penelitian: Penelitian ini merupakan quasi-experimental dengan rancangan pre and post test with control group design. Sampel dalam penelitian ini berjumlah 25 ibu hamil trimester III. Teknik pengambilan sampel menggunakan teknik purposive sampling. Instrumen penelitian menggunakan kuesioner DASS 42. Hasil uji normalitas data berdistribusi normal sehingga dianalisis data menggunakan uji paired t-test.Hasil Penelitian: Hasil penelitian menunjukan bahwa skor rata-rata kecemasan ibu sebelum terapi 13,48 (Sedang) sedangkan sesudah terapi menjadi 7,88 (normal). Hasil uji bivariate didapatkan p value 0,000.Kesimpulan: Terapi Spiritual Emotional Freedom Technique (SEFT) mampu mengatasi kecemasan ibu hamil dalam menghadapi persalinan.Saran: Diharapkan terapi ini dapat diaplikasikan dalam praktik kebidanan perawatan ibu hamil khususnya ibu hamil yang mengalami trauma atau mempunyai kecemasan dalam kehamilannya. Kata kunci: Kecemasan, ibu hamil, Terapi Spiritual Emotional Freedom Technique